(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim of the study: To asses the nurses’ knowledge about pulmonary embolism Methodology: A descriptive design study was carried out for the period of November18th 2018 up to the 20th of April 2019. Anon-probability (purposive) samples of (60) a nurse work at respiratory care unit in Baghdad Teaching Hospitals from different educational levels, both sexes ( males and females), were selected. The instrument questionnaire tool consist of two parts, First part consist of (6) items included, age, gender, level of education, number of years of employment in hospital, number of experience in the respiratory care unit and training course about pulmonary embolism.& second part consist of (4) domains which included Nurses knowledge concerning definition and causes of disease, signs and symptoms, diagnostic test ,treatment of pulmonary embolism. The data have been analyzed through the application of: descriptive and the inferential analysis, and the researcher used the SPSS version 20 to analysis of data. Conclusion: The study recommend that the critical care nurse have moderate level of knowledge and there were significant association between level of education and the nurse knowledge at p > 0.05 level.